Pertanggungjawaban Pidana Korban dan Batas Pembelaan Diri dalam Kasus Jambret Sleman - Djamaludin Djamaludin; Iryana Anwar (Kertha Wicaksana, 2026)
Debates on the criminal liability of victims who react to an ongoing attack have gained renewed relevance following the enactment of the Indonesian National Criminal Code. The Sleman robbery case, where the victim’s husband was designated a suspect after the perpetrator died during a pursuit, exposes tension between culpability doctrine, self-defense, and law enforcement practice. Prior scholarship has addressed these issues mainly at a conceptual level, with limited focus on the construction of victim liability in concrete post-reform contexts. This normative legal study employs statutory and conceptual approaches to analyze provisions on self-defense, excessive self-defense, and culpability under the National Criminal Code, supported by victimological perspectives. The findings indicate a shift from fault-based liability toward causal liability that risks producing secondary victimization and widening the gap between legal reform and enforcement. Proper assessment of self-defense should therefore function as a preliminary threshold of culpability to preserve the protective role of criminal law.